2007
DOI: 10.1021/jp710189p
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Strained Pore Wall Structure in Mesoporous Silica FSM-16 Studied by X-ray Absorption Spectroscopy

Abstract: The local structure around Si species in mesoporous silica FSM-16 was investigated by Si K-edge XAFS. As expected from the previous studies, the local symmetry of Si species in FSM-16 is almost identical to that of amorphous silica. The Si−O bond length was longer than those of α-quartz, ZSM-5, and amorphous silica. Relations between the prolonged bond length and the acidic property of FSM-16 were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…As an active site for the acid catalyzed reaction on FSM-16, we have proposed that weakly perturbed isolated silanol groups acted as Brønsted acid sites [6], and strained siloxane bridges acted as Lewis acid site [9]. Evidence of a strained pore wall structure in FSM-16 had been confirmed by XAFS characterization [20]. The siloxane-bridges could connect to form rings inside the pore wall.…”
Section: Dependence Of Pore Size On Surface Aciditymentioning
confidence: 83%
See 1 more Smart Citation
“…As an active site for the acid catalyzed reaction on FSM-16, we have proposed that weakly perturbed isolated silanol groups acted as Brønsted acid sites [6], and strained siloxane bridges acted as Lewis acid site [9]. Evidence of a strained pore wall structure in FSM-16 had been confirmed by XAFS characterization [20]. The siloxane-bridges could connect to form rings inside the pore wall.…”
Section: Dependence Of Pore Size On Surface Aciditymentioning
confidence: 83%
“…The acidic properties were found to closely relate to the hydration state of FSM-16, and then we proposed that weakly perturbed silanol groups act as Brønsted acid sites and a strained siloxanebridge formed by dehydration of isolated silanol groups acting as a Lewis acid site [6,9]. Recent Si K-edge XAFS characterization of FSM-16 [20] revealed that the averaged Si-O bond length was longer than those of a-quartz, ZSM-5, and amorphous silica. Then, it was also proposed that strained siloxane bridges exist inside the pore wall of FSM-16 intrinsically, which are responsible for the Lewis acid sites.…”
Section: Introductionmentioning
confidence: 94%
“…Possibly similar acid-species would be formed on the surface of 10-20 wt% WO3 _ ZrO2 calcined at 1073 K, with the surface concentration corresponding to the theoretical monolayer. 39) Amorphous silica is known to be catalytically inert because of the weak acidity of silanol groups. However, siliceous hexagonally ordered mesoporous silicas such as FSM- 16 40 .…”
Section: )mentioning
confidence: 99%
“…We assume that the acidic property of FSM-16 originates from the characteristic ordered pore structure with thin walls 52),53) that permits the existence of strained siloxane bridges, which would induce Brønsted acidity in the silanol groups. To confirm the presence of the strained pore structure and verify our acidity generation hypothesis of siliceous mesoporous silicas, the coordination environments of Si species in various types of silicas were investigated by Si _ K edge X-ray absorption spectroscopic techniques 39) . Figure 11 shows the Si K-edge XANES spectra of silica materials and the first derivatives.…”
Section: )mentioning
confidence: 99%
“…Data reduction for the EXAFS analysis was performed with the REX2000 program. 25 For the XANES, background removal and normalization of the spectra were performed using the Igor Pro 6.2 program 26 according to the procedure reported by Tanaka et al 27 A quantitative component analysis for the XANES spectra by a least-squares method was also performed with Microsoft Excel 2010. The phase shift and backscattering amplitudes were calculated using the FEFF8.4 program.…”
Section: Introductionmentioning
confidence: 99%